2008
DOI: 10.1038/bmt.2008.325
|View full text |Cite
|
Sign up to set email alerts
|

Poor outcome in post transplant lymphoproliferative disorder with pulmonary involvement after allogeneic hematopoietic SCT: 13 years' experience in a single institute

Abstract: EBV-induced post transplant lymphoproliferative disorder (PTLD) continues to be a major complication after transplantation. Between January 1993 and April 2006, 12 cases of B-cell lymphoproliferative disorder were identified among 577 patients after allogeneic hematopoietic SCT (HSCT) with an overall incidence of 2.51% at 1 year. Grades II-IV acute GVHD, CMV antigenemia and the use of antithymocyte globulin (ATG) were independent risk factors for PTLD. At diagnosis, all of the tumors were CD20-positive and 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 33 publications
(24 reference statements)
1
30
1
Order By: Relevance
“…When progressing further, organ involvement is possible often featuring severe hepatitis, pneumonia, colitis, nephritis and variable symptoms associated with central nervous system manifestation. 5,27 In the laboratory, increasing levels of the lactate dehydrogenase regularly herald the clinical manifestation of PTLD. In cases of liver involvement, increased liver enzymes may be diagnosed as a surrogate of EBV hepatitis.…”
Section: Clinical and Laboratory Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…When progressing further, organ involvement is possible often featuring severe hepatitis, pneumonia, colitis, nephritis and variable symptoms associated with central nervous system manifestation. 5,27 In the laboratory, increasing levels of the lactate dehydrogenase regularly herald the clinical manifestation of PTLD. In cases of liver involvement, increased liver enzymes may be diagnosed as a surrogate of EBV hepatitis.…”
Section: Clinical and Laboratory Presentationmentioning
confidence: 99%
“…2,3 Published experience regarding the incidence of EBV-PTLD after allogeneic HCT ranges between 0.5 and 17% and is mainly based on single-centre experiences or retrospective studies limited by small numbers and diverse patient characteristics. [4][5][6][7] However, Landgren et al 8 collected data on 127 EBV-PTLD cases from 271 centres and found an elevated risk for developing PTLD especially in the first year after HCT (83%) with the highest occurrence during the first 6 months. However, late EBV-PTLD could be observed even up to 10 years after HCT.…”
Section: Introductionmentioning
confidence: 99%
“…1,[6][7][8][9][10][11][12] In the largest study to date, which included 26 901 allogeneic HCT recipients, the cumulative incidence of PTLD was 0.2% with no T-cell depletion, 2.8% with selective (B lymphocyte sparing) T lymphocyte depletion of grafts ex vivo and 1.7% in patients receiving ATG as in vivo T lymphocyte depletion for GvHD prophylaxis or treatment. 1 In the published studies, diagnostic criteria for PTLD and strategies for its prevention varied or were not described.…”
Section: Introductionmentioning
confidence: 99%
“…15 Mortality rates of PTLD have been reported between 50 and 100%, although it is not always clear whether PTLD was the primary or secondary cause of death, or an incidental finding at autopsy. 7,10,11,16 Mortality rates appear to be lower if intervention (tapering immunosuppression or administering rituximab or donor lymphocytes) occurs prophylactically (at a specified post transplant time point, irrespective of EBV reactivation) or preemptively (at the time of EBV viremia exceeding a threshold) rather than after PTLD has been diagnosed. 15 However, prophylactic or preemptive intervention subjects patients who would not develop PTLD to the side effects and costs of the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…9, 13-15 PTLD with extranodal involvement carries worse prognosis than those with isolated lymphnode involvement, which might result from the difficulty in early diagnosis and low concentrations of medication distributed in affected tissues, 16, Downloaded by [University of Pennsylvania] at 13: 10 28 March 2016 progression and poorer survival. Our results also revealed that the patients with extranodal involvement were less responsive to rituximab than those with isolated lymphnode involvement, but had a higher response rate than those with extranodal involvement in reports, 14,18 which might be attributed to early diagnosis and prompt treatment as well as special medication approach. In our centers, EBV-DNA monitoring is routinely performed, which is helpful to early diagnose PTLD.…”
Section: Discussionmentioning
confidence: 43%